Third Wave : The New Russian Poetry - Johnson, Kent (University of Michigan)
Contiene poesía de Tatiana Shcherbina, Alexei Parshchikov, Vladimir Druk, Ilya Kutik, Arkadii Dragomoshchenko, Nina Iskrenko, Dimitri Prigov, Sergei Gandlevsky, Olga Sedakova, Lev Rubinshtein, Nadezhda Kondakova, Ivan Zhdanov, Andrei Turkin, Vladimir Aristov, Pavel Papperstein, Mikhail Aizenberg, Elena Shvarts, Timur Kibirov, Viktor Krivulin, Yuri Arabov, Aleksandr Eremenko.